The relationship between social support and learning engagement among Chinese preschool teacher trainees: the chain mediating effect of psychological capital and professional identity - Zhang, Meng; Wang, Guanghua; Li, Li (Frontiers in Psychology, 2025)
IntroductionThe development of the teaching workforce serves as a cornerstone of China’s strategy to become an educational power. In the context of demographic structural transformation, the cultivation of preschool education teachers faces new demands posed by the contemporary era. Investigating the learning engagement of preschool teacher trainees and exploring the influencing factors and their mechanisms of action are of significant importance for enhancing the learning quality of these students.MethodsData were collected from 1,160 preschool teacher trainees in Shanghai, China, via four scales: social support scale, the psychological capital scale, the professional identity scale, and the learning engagement scale. This study employed SPSS and Model 6 of the SPSS macro program PROCESS 4.0 to analysis and test.ResultsSocial support is positively associated with learning engagement among preschool teacher trainees (β = 0.611, p < 0.001). Psychological capital can play a mediating role between social support and the learning engagement of preschool teacher trainees, with the mediating effect accounting for 36.99%. Professional identity can play a mediating role between social support and the learning engagement of preschool teacher trainees, with the mediating effect accounting for 11.78%. Social support can influence learning engagement through the chain mediating pathway of “psychological capital → professional identity,” with the mediating effect accounting for 31.59%.DiscussionFindings underscore the protective role of social support, psychological capital, and professional identity in academic contexts, suggesting that it promotes the learning engagement among preschool teacher trainees. Accordingly, this study proposes a tripartite educational model encompassing “external support—psychological empowerment—identity construction” to optimize the practices of talent cultivation for preschool teacher trainees.